2020
DOI: 10.1155/2020/8789275
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Bone Marrow Plasma Cytokine Signature Profiles in Severe Aplastic Anemia

Abstract: Objective. We studied bone marrow plasma (BMP) cytokines in severe aplastic anemia (SAA) patients and healthy volunteers to investigate differences in the cytokine profiles between them and propose a cytokine signature of SAA. Methods. A Bio-Plex suspension array system was used to measure 27 analytes in BMP samples from 47 SAA patients and 30 healthy donors. Results. Compared to healthy people, SAA patients had higher levels of tumor necrosis factor α (TNF-α), interferon-γ (IFN-γ), interleukin-2 (IL-2), monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The number of Th1 cells in treatment-naive SAA patients increased significantly, and the cytokines (e.g. INF-γ, TNF-α and IL-2) associated with Th1 cells increased significantly ( 7 ). The above factors together lead to excessive activation of cytotoxic T lymphocytes (CTLs).…”
Section: Introductionmentioning
confidence: 99%
“…The number of Th1 cells in treatment-naive SAA patients increased significantly, and the cytokines (e.g. INF-γ, TNF-α and IL-2) associated with Th1 cells increased significantly ( 7 ). The above factors together lead to excessive activation of cytotoxic T lymphocytes (CTLs).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the etiology and pathogenesis of SAA have remained to be fully elucidated. Previous studies by our group have confirmed that various immune cells and cytokines constitute an abnormal immune status in patients with SAA (20,21), including the involvement of Th1/Th2 subset imbalances, hyperfunctional CTLs, insufficiencies in the regulatory T and NK cell populations and negative hematopoietic cytokines (22,23). These subsequently induce excessive apoptosis of CD34 + HSCs and inhibit hematopoietic colony formation through the perforin, granzyme B, Fas/FasL and the TNF-related apoptosis-inducing ligand pathways (13).…”
Section: Discussionmentioning
confidence: 70%
“…BM mesenchymal stem cells (BM-MSCs) might be involved in the pathogenesis of AA, because MSCs can differentiate in distinct types of stromal cells that support hematopoiesis and regulate immune cells in the BM niche [ 52 , 53 , 54 , 55 , 56 ]. BM-MSCs have reduced ability to suppress proliferation and differentiation of CD4 + cells, and TNF-α and IFN-γ production in AA while inducing Treg polarization without affecting IL-4, IL-10, or IL-17 production.…”
Section: Acquired Aplastic Anemiamentioning
confidence: 99%
“…Other highly expressed genes are Th1, Th2, and Th17 differentiation-associated and inflammation-related genes. In addition, abnormal splicing is also documented and involved genes are related to oncogenesis, metabolism, and other signaling pathways such as mTOR (mammalian target or rapamycin) and Wnt [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Acquired Aplastic Anemiamentioning
confidence: 99%